A review on material design, performance, and practical application of electrically conductive cementitious composites. (30th December 2019) - Wang, Lining; Aslani, Farhad
Highlights: Design of filler content should be based on the percolation threshold theory. Percolation threshold theory helps to avoid inadequate use of fillers. Manufacturing process alters the properties of the cementitious composite. The review reported the results of various studies. Factors affecting the electrical performance were discussed. Abstract: Electrically conductive cementitious composite (ECCC) possesses the functional properties of high conductivity and strain/stress sensitivity, thus can be used as an electrical heater for snow melting/de-icing, a conductive component for grounding system or cathodic protection system and achieve health monitoring or traffic detection instead of using embedded, attached or remote sensors. The critical component of ECCC is functional filler, which can be used to endow cementitious composite with high conductivity and piezoresistivity. Besides that, the included functional fillers can also enhance the mechanical properties, durability, permeability and increase the electromagnetic shielding effect of the composite. More than ten single and hybrid functional fillers and their effects on electrical, mechanical and microstructure properties of cementitious composite are reviewed in this paper. The review reveals that the design of functional filler content should be based on the percolation threshold theory, since it helps to identify the optimal filler content to avoid insufficient or excessive use of fillers, which may lead to poor electrical performance and filler dispersion. Besides, the manufacturing process, such as the filler dispersion, curing condition and moulding methods is also closely related to the filler distribution, hydration process and water content which consequently alters the electrical and mechanical properties of cementitious composite. The review reported the results of various studies and discussed factors affecting the electrical performance of cementitious composite. It is expected that this review can provide a direction for new researchers to explore and engage in related research and provide insight for experienced researchers to explore the development prospect based on ECCC.